Recurrence of Chronic Subdural Hematoma Is Independent of ABO Blood Type: A Retrospective Cohort Study - Ou, Yunwei; Yu, Xiaofan; Wu, Liang; Zhang, Dong; Liu, Weiming (Frontiers in Neurology, 2022)
Objective: A previous study with the limited number of patients has showed that blood type A was a risk factor for the recurrence of CSDH. The primary objective of this study was to investigate the association between the recurrence of CSDH and ABO blood type based on a larger sample size. Methods: The authors reviewed inpatients with symptomatic CSDH from August 2011 to August 2021. Hospitalization information and data on long-term outcomes and recurrence among these patients were gathered. For all clinical variables, numbers (percentages) and mean ± standard deviations were used for categorical and continuous variables, respectively. For intergroup comparisons, the 2 test or one-way ANOVA was carried out. Multivariable logistic regression analyses were performed to identify the association between CSDH recurrence and blood types. Results: We included 1,556 inpatients in this study. The recurrence rate of CSDH showed no differences among different blood types. In the multivariable logistic regression analyses, ABO blood type (A: OR 1.064, 95% CI 0.467-2.851, p = 0.793; B: OR 0.682, 95% CI 0.315-1.269, p = 0.164; AB: OR 0.537, 95% CI 0.426-1.861, p = 0.357) was not a significantly independent predictor of CSDH recurrence. Conclusions: Our study demonstrated that ABO blood type was not a risk factor for the recurrence of CSDH. Thus, we should not pay too much attention to ABO blood type in terms of CSDH recurrence.